Bioethics journals: Are there many? Are there few? What the situation is? - Hossne, William Saad [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
This work presents a bibliometric profile of Bioethics Journal according to the following journal databases: MEDLINE, LILACS, The Philosopher' s Index, Ulrich's, SciELO and Qualis classification system (Brazil). We found that: From 38 titles indexed in MEDLINE, 25 (66%) still exist; the country with the highest number is the U.S.A (36%); most Bioethics journals appeared in the 1990's (47%), and 36% have less than 10 years of existence. From those that disappeared (34%), the average survival time was about 4 years. There are only 12 countries with indexed journals. In Brazil, from 3 Bioethics journals, only one is (partially) indexed. English is the preponderant language (45%). Only 3% of journals are monthly. LILACS has two additional publications (Acta Bioethica, Chile, and Revista Latino Americana, Colombia). SciELO has only Acta Bioethica. In Ulrich's database, there are eight additional publications. In Qualis classification system there are four journals.
Periódicos de bioética. ¿Hay muchos? ¿Hay pocos? ¿Cuál es la situación?
Keywords: Bibliometric profile; Bioethics-publications; Databases; Scientific journal